Evaluation of feeding budgeting strategy or complete diet blending on finishing pig growth performance and carcass characteristics - Frobose, H.L.; Ryder, D.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 252 mixed-sex pigs (PIC 327 × 1050; initial BW = 79.8 ± 0.9 lb BW) were used in a 95-d growth study to compare feed-budgeting strategies and complete diet blending for finishing pigs on growth performance, carcass characteristics, and economics. Feed was delivered to all pens of pigs using a computerized feed delivery system (FeedPro, Feedlogic Corp., Willmar, MN) that is capable of delivering and dispensing 2 separate diets. Four experimental treatments had 9 pens/treatment and 7 pigs/pen in a randomized complete block design. Dietary treatments included: (1) standard 4-phase (0.91, 0.77, 0.67, and 0.61% standardized ileal digestible [SID] lysine, respectively) complete feed program (Standard), (2) blending a high- and low-lysine complete diet to meet the estimated daily SID lysine requirement from d 0 to d 95 (Curve), (3) Treatment 1 diets with 20% greater feed budget allowance per phase (Over), and (4) Treatment 1 diets with 20% lower feed budget allowance per phase (Under). Diets were corn-soybean meal–based with no added fat. The standard diet was budgeted at 117, 138, 158, and 175 lb for Phases 1 through 4, respectively. Overall (d 0 to 95), no differences (P ≥ 0.11) were observed in ADG, ADFI, F/G, or final BW among pigs fed the budgeting strategy diets. Pigs phase-fed a standard phase-feeding program tended to have heavier (P = 0.09) HCW than pigs fed the Curve and tended to have (P = 0.10) greater percentage carcass yield than those fed the Curve or the Over diet. No differences (P ≥ 0.14) were observed in percentage lean, fat depth, or loin depth. Pigs fed diets blended to a lysine curve had lower feed costs (P < 0.004) than all three phase-feeding treatments, but because of heavier HCW, pigs fed the standard feed budget had greater (P = 0.05) revenue per pig and tended to have greater (P = 0.10) income over feed cost (IOFC) under two separate diet and carcass price scenarios compared with pigs fed with the Curve, with pigs over- and under-budgeted remaining intermediate. Over- and under-budgeting situations in phase feeding programs had minimal impact on growth performance, carcass characteristics, and net returns; furthermore, feeding blended diets to a lysine curve did not improve growth performance and led to lower total revenue than using a standard feed budget.
Keywords: Swine; Feed blending; Feed budgeting; Finishing pig; Phase-feeding